Morfologi Kawasan Dan Tipologi Rumah Adat Kampung Mahmud Kabupaten Bandung - Widiana, Fenny (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2018)
Indonesia is an archipelago country that has diverse ethnic, cultural and customs. Thediversity is reflected in the environment and traditional buildings of indigenous villagesin each region. Currently, there are still some areas that still have and maintain thetraditional village. One of them is the area of West Java. Kampung Mahmud is a periurbanvillage in the city of Bandung. Kampung Mahmud has located in the village ofMekarrahayu Margaasih district of Bandung. Still retaining customs with respect toKaruhun (ancestors) is the hallmark of this village. The modernization and constructionof the bridge by the government in 1997 has influenced changes in Mahmud village bothmacro on the region and micro on the building. This paper aims to find out the morphologyof Kampung Adat Mahmud area and to know Typology of traditional house ofMahmud village. The method used in this paper is descriptive qualitative. The data collectionmethod was conducted by literature study from journal and book about the theoryof typology, morphology as well as about the traditional village of Mahmud. Data analysismethod using diachronic and synchronous approach. The results obtained that themorphology of Mahmud customary village area in the form of orientation and the additionof building period. The orientation which initially centered on the mosque as a placeof worship turned into centered toward the ancestral grave and then to the connectingroad. While the typology of house building is influenced by climate factor, culture, environment,building technique, customary law, religion, and social relation of society.Â DOI: https://doi.org/10.26905/lw.v10i2.2679